The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.physletb.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

A small non-vanishing cosmological constant from the Krein–Gupta–Bleuler vacuum

Abstract: We point out a potential relevance between the Krein-Gupta-Bleuler (KGB) vacuum leading to a fully covariant quantum field theory for gravity in de Sitter (dS) spacetime and the observable smallness of the cosmological constant. This may provide a formulation of linear quantum gravity in a framework amenable to developing a more complete theory determining the value of the cosmological constant.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In the KGB context, despite the presence of negative norm sates in the theory, the energy operator is positive in all physical states, and vanishes in the vacuum. Recently, a preliminary estimate of the expected order of magnitude of vacuum energy density stored in the cosmological constant today with respect to the KGB vacuum, presented in [39], has been shown that the obtained result demonstrates a remarkable coincidence with the observational data. This coincidence seems to be almost too good to be just an accident.…”
Section: Discussionsupporting
confidence: 54%
“…In the KGB context, despite the presence of negative norm sates in the theory, the energy operator is positive in all physical states, and vanishes in the vacuum. Recently, a preliminary estimate of the expected order of magnitude of vacuum energy density stored in the cosmological constant today with respect to the KGB vacuum, presented in [39], has been shown that the obtained result demonstrates a remarkable coincidence with the observational data. This coincidence seems to be almost too good to be just an accident.…”
Section: Discussionsupporting
confidence: 54%
“…• In the semiclassical description of general relativity (Λ > 0) when matter field is present, a preliminary estimate of the expected order of magnitude of vacuum energy density stored in the cosmological constant today with respect to the KGB vacuum yields a remarkable coincidence with the empirical data [57].…”
Section: Discussionmentioning
confidence: 73%
“…As a direct consequence, the vacuum energy of the free field in this construction automatically vanishes, Ω|T 00 |Ω = 0. This property has an interesting link to the cosmological constant problem (see [57]).…”
Section: B Quantum Observablesmentioning
confidence: 99%
“…To see more on this automatic renormalization procedure and its physical consequences, readers are referred to Refs. [123,124].…”
Section: Stress Tensormentioning
confidence: 99%